The Influence of Instagram Social Media and Creativity on Learning Outcomes to Design Party Clothes at State 3 Vocational School Manado - Langguna, Ayu Patricya; Daud, Metsi; Olii, Djami; Rompas, Parabelem Tinno Dolf (International Journal of Information Technology and Education, 2023)
This research aims to: 1) Find out the creativity in designing party clothing before using Instagram social media for students in SMK NEGERI 3 Manado. 2) Knowing the creativity in designing party clothes after using social media Instagram for students in SMK NEGERI 3 Manado. 3) Knowing the influence of the use of social media Instagram and creativity on student learning outcomes in designing student party clothing at SMK NEGERI 3 Manado. The sampling technique in the research was a saturated sample consisting of 35 students. Validity The instrument uses this validity with valid results. The reliability of the instrument using Cronbach's Alpha was 0.93 and 0.88. The normality test uses Kolmogorov-Smirnov with values 0.657>0.224 and 2.619>0.224. The linearity test obtained Y=42.886723 and Y=35.05175+0.598818. Hypothesis testing produces P-Value> 0.05 so Ho is accepted and Ha is rejected. Research results show: 1) Creativity in designing party clothes before using Instagram social media was an average of 70 in the less creative category. 2) Creativity in designing party clothes after using social media Instagram averaged 86 in the creative category. 3) The influence of the use of social media Instagram and creativity on student learning outcomes in designing party clothing can be seen in the increase in students' report card scores, which before use averaged 70 and after use averaged 85. Based on the results of the hypothesis test, it was stated that there was an influence.